The lanthanides and actinides : synthesis, reactivity, properties and applications - Liddle, Stephen T. (Stephen Taylor); Mills, David P.; Natrajan, Louise S. (New Jersey : World Scientific, 2022)
"The Lanthanides and Actinides: Synthesis, Reactivity, Properties and Applications constitutes an introduction to and comprehensive coverage of f-block chemistry encompassing the following areas: periodicity, natural occurrence and extraction, separations, electronic structure, coordination chemistry, organometallic chemistry, small molecule activation, catalysis, organic synthesis applications, magnetism, spectroscopy, computation, materials, photonics, solar cell technology, biological imaging, and technological applications. Under these subject areas the book provides a broad but deep coverage, providing basic overviews as well as detailed chapters on specific areas. This book, targeted at academics, postgraduates and advanced undergraduates, will serve as an ideal introductory text and key reference work to the Lanthanides and Actinides"--
Includes bibliographical references.
Keywords: Rare earth metals; Actinide elements